Numerical And Experimental Investigations Of The Oscillatory Flow Inside Standing Wave Thermoacoustic System At Two Different Flow Frequencies - Mohd Sa'at, Fatimah Al-Zahrah; Shikh Anuar, Fadhilah; Mustaffa, Siti Hajar Adni (Penerbit Akademia Baru, 2019)
Energy crisis has led to the search of sustainable and green technology and thermoacoustics have been recognised as one of them. One of the challenging issue with this emerging technology is the difficulty in understanding the complex fluid dynamics phenomena of the oscillatory flow of the acoustic wave inside the system. In this paper, computational fluid dynamics (CFD) models of a standing wave thermoacoustic flow conditions are solved using ANSYS Fluent and the CFD results are validated with experimental data from a similar setup; standing wave flow conditions with two resonance frequencies of 13.1 Hz and 23.1 Hz. Good match of velocity amplitude data was found between the CFD and the experimental results, particularly for the low flow frequency of 13.1 Hz. Similar trend of velocity results between numerical models and experimental results of higher frequency of 23.1 Hz is also observed. As frequency increases, the velocity amplitude did not change much but the displacement of fluid becomes smaller. This causes the vortex to travel rapidly but at a shorter distance into and out of the channel when the fluid flows at higher frequency of 23.1 Hz. The amplitude of annular flow also becomes closer to the wall because the viscous penetration depth becomes thinner as frequency increases. These results help in understanding the impact of frequency variations on fluid dynamics aspect of the standing wave inside the emerging technology of thermoacoustic systems.